Menimbang ekonomi Islam keuangan publik, konsep perpajakan dan peran bait al.mal Sabchuddin Azmi ; penerjemah, Widyawati ; editor, Munir, Mathori A. Elwa - AZMI, Sabchuddin; Widyawati; Munir; Elwa, mathori A (Nuansa, 2005)
232 hlm. ; 21 cm